Modelling beam-column joints and FRP strengthening in the seismic performance assessment of RC existing frames. (10th May 2016) - Del Vecchio, Ciro; Di Ludovico, Marco; Prota, Andrea; Manfredi, Gaetano
Abstract: The recent seismic events demonstrated that the high vulnerability of existing RC structures is often related to the joint subassemblies shear failure which may lead to the collapse of the entire structural system. However, most of the available computer programs do not properly account for this aspect. This paper deals with the numerical seismic assessment of RC structural systems designed without proper seismic details in the joint panel and the benefits of the FRP local strengthening. A new modelling strategy has been developed to account for the joint nonlinear behaviour and the fiber reinforced polymer (FRP) strengthening in the finite element method (FEM). Several case studies were selected for the model validation. At the subassembly level, the model predictions were compared with recent experimental tests on full-scale beam-column joints with and without FRP strengthening. At the structure level, a case study building damaged in the joints during the L'Aquila earthquake and then retrofitted with FRP systems was analyzed. The predicted structural performances and structural damages were compared with observational data. Furthermore, the benefits of the joint FRP strengthening on the global seismic performances were numerically assessed.